Toward Evidence-Based Standards for Spiritual Care in Chronic Illness: A Comprehensive Literature Review - Manisha; Wisuda, Aris Citra; Sansuwito, Tukimin bin; Ahmed, Idris Adewale (International Journal Scientific and Professional, 2025)
Spiritual care is a vital component of holistic nursing, particularly for patients with chronic and life-limiting illnesses. It addresses existential suffering and supports emotional, psychological, and spiritual well-being. This review aims to identify and synthesize evidence-based standards for spiritual nursing care in patients with chronic illnesses, particularly those in palliative care settings. A comprehensive literature review was conducted using six databases PubMed, ProQuest, DOAJ, ScienceDirect, Garuda, and Google Scholar focusing on peer-reviewed articles published between 2018 and 2024. Articles were selected based on predefined inclusion and exclusion criteria to ensure relevance and quality. The findings highlight several key standards in spiritual nursing care: acknowledging and respecting patients' spiritual beliefs, offering compassionate emotional and psychological support, and fostering meaning and hope at the end of life. The literature consistently emphasizes the need for an individualized, culturally sensitive, and holistic approach. Integrating spiritual care into routine palliative nursing practice has been shown to improve coping, reduce distress, and enhance overall quality of life for chronically ill patients. Addressing the spiritual needs of patients with chronic illness is essential for delivering comprehensive, patient-centered care. Developing evidence-based spiritual care standards can enhance the effectiveness of palliative care and support patients in achieving peace, meaning, and well-being.